Internalization of Discipline Values Through School Culture in Student Character Building at MTsN 2 Mandailing Natal - Ilmi Wahyuni; Kulsum Rahmayani; Nur Asiah Nasution; Rian Azhari; Siti Mulyana Lubis; Ayu Meita Puteri Siregar (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the process of internalizing disciplinary values ​​through school culture and its impact on student character formation at MTsN 2 Mandailing Natal. This study used a qualitative approach with a case study design. Data were obtained through participatory observation, in-depth interviews with the principal, teachers, and students, and documentation. The data analysis technique used the interactive model of Miles, Huberman, and Saldaña, which was carried out continuously through the stages of data condensation, data presentation, and drawing and verifying conclusions. In the data condensation stage, the researcher selected, focused, and grouped data according to the research theme. Next, the data were presented in the form of descriptive narratives to make the relationships between findings easier to understand. The final stage was carried out through drawing and verifying conclusions to ensure the consistency and validity of the data based on the results of observations, interviews, and documentation. The research findings indicate that internalization of disciplinary values ​​is carried out through habituation, teacher role models, and reinforcement through a system of rewards and sanctions. A consistent school culture has been proven to be able to shape the character of students who are more disciplined, responsible, independent, and have prosocial behavior in the madrasah environment.